Direct power control of the PWM rectifier using sliding mode control. (1st January 2011) - Barkat, Said; Tlemçani, Abdelhalim; Nouri, Hassan
This paper presents the analysis and design of the direct power control of a boost PWM rectifier based on sliding mode control. In the aim to improve control performance of the rectifier, the proposed approach combines the merits of sliding mode control, direct power control and space vector modulation. The resulting control scheme is able to drive the output dc voltage to the desired value while keeping a sinusoidal input phase control with a unity power factor. The feasibility and effectiveness of the considered control structure has been examined by computer simulations.